Numerical testing and verification of a marine propeller operating in a uniform flow field. (7th February 2021) - Kim, Howan; Leong, Zhi Quan
ABSTRACT: This paper examines the methodology for the Reynolds Averaged Navier-Stokes (RANS) based Computational Fluid Dynamics (CFD) prediction of the flow around a propeller operating in a uniform flow. The work investigates the influence of grid and physics setup on the prediction of propeller propulsion properties (i.e. thrust ( Kt ) and torque ( Kq ) coefficients). The investigation includes the selection of the turbulence model, near wall gridding and state condition to achieve predictions comparable to experimental measurements. The prediction was validated against the experimental data from the open water propeller test conducted at the Australian Maritime College Cavitation Tunnel (AMCCT). The results show the CFD predictions were in good agreement with the experimental measurements (i.e. less than 5% at up to J = 1.1 and 10% at up to J = 1.19 for Kt and Kq ). This confirms the presented methodology can be adopted to provide high fidelity prediction for the hydrodynamic characteristics of the propeller.